Petrographical, petrochemical investigation of Sandikli volcanic and usability of these rocks as trass, in Afyon region (Western Anatolia), Turkey - ÖZPINAR, YAHYA (Bulletin of the Geological Society of Greece, 2001)
Investigated area and its surrounding district consist of volcanic rocks. The Sanduklu volcanic are mainly composed of lavas, tuffs and tuffits. Using to K-Ar age method, the age of Sanduklu Lavas have been dated and ranged from 14 ± 0.3-8.0 to ± 0.6 Ma (Ercan, 1986).On the basis of diagrams Si02-(K20+Na20), Log (Zr/ TiO2*0.0001)-SiO2, Nb/Y-Log (Zr/TiO2*0.0001) and Ti02-Zr lavas are thrachyandesite, phonolitic tefrite, basaltic andésite, basaltic thrachy-nephelinite, andésite and dacite. Tuffs have been widely zeolitizated and dominant zeolite minerals are chabazite and phillipsite. Three phillipsite form were determined. These are potassiumsodium-aluminum-silicate hydrate, sodium-aluminum-silicate hydrate and potassium-calcium-silicate-silicate hydrate. The chemical and technological tests of zeolitic tuffs, altered lavas and tuffits were carried out and they are suitable to trass standards in cement industry.